Smart Biopolymer Scaffolds Based on Hyaluronic Acid and Carbonyl Iron Microparticles: 3D Printing, Magneto-Responsive, and Cytotoxicity Study - Gorgol, Danila; Mrlík, Miroslav; Mikulka, Filip; Víchová, Zdenka; Mahelová, Leona; Ilčíková, Markéta; Minařík, Antonín (ACS applied bio materials, 2024)
This study deals with utilization of the hyaluronic acid (HA) and carbonyl iron (CI) microparticles to fabricate the magneto-responsive hydrogel scaffolds that can provide triggered functionality upon application of an external magnetic field. The various combinations of the HA and CI were investigated from the rheological and viscoelastic point of view to clearly show promising behavior in connection to 3D printing. Furthermore, the swelling capabilities with water diffusion kinetics were also elucidated. Magneto-responsive performance of bulk hydrogels and their noncytotoxic nature were investigated,, and all hydrogels showed cell viability in the range 75-85%. The 3D printing of such developed systems was successful, and fundamental characterization of the scaffolds morphology (SEM and CT) has been presented. The magnetic activity of the final scaffolds was confirmed at a very low magnetic field strength of 140 kA/m, and such a scaffold also provides very good biocompatibility with NIH/3T3 fibroblasts.
Keywords: hydrogely; Hyaluronic Acid; testování materiálů; 3D printing; biokompatibilní materiály; NIH 3T3 Cells; Particle Size; scaffold; Mice; buňky NIH 3T3; zvířata; karbonylové sloučeniny železa; kyselina hyaluronová; magnetic particles; Iron Carbonyl Compounds; 3D tisk; Tissue Scaffolds; Cell Survival; Biocompatible Materials; viabilita buněk; biopolymery; velikost částic; tkáňové podpůrné struktury; myši; Printing, Three-Dimensional; Hydrogels; Animals; magneto-responsive; Materials Testing; hyaluronic acid; Biopolymers